Inner-Shell-Ionization-Induced Femtosecond Structural Dynamics of Water Molecules Imaged at an X-Ray Free-Electron Laser - Jahnke, T.; Guillemin, R.; Inhester, L.; Son, S.-K.; Kastirke, G.; Ilchen, M.; Rist, J.; Trabert, D.; Melzer, N.; Anders, N.; Mazza, T.; Boll, R.; et al. (My University, 2021)
The ultrafast structural dynamics of water following inner-shell ionization is a crucial issue in high-energy radiation chemistry. We have exposed isolated water molecules to a short x-ray pulse from a free-electron laser and detected momenta of all produced ions in coincidence. By combining experimental results and theoretical modeling, we can image dissociation dynamics of individual molecules in unprecedented detail. We reveal significant molecular structural dynamics in H2O2+, such as asymmetric deformation and bond-angle opening, leading to two-body or three-body fragmentation on a timescale of a few femtoseconds. We thus reconstruct several snapshots of structural dynamics at different time intervals, which highlight dynamical patterns that are relevant as initiating steps of subsequent radiation-damage processes.